2019
DOI: 10.18502/ijm.v11i5.1960
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc supplementation on pro-inflammatory cytokines (TNF-α, IL-1 AND IL-6) in mice with Escherichia coli LPS-induced diarrhea

Abstract: Background and Objectives: Inflammation in the intestine causes diarrhea due to an increased release of pro-inflammatory cytokines such as TNF-α, IL-1, and IL-6. These are triggered by the exposure of E. coli-LPS to epithelial cells of the intestinal mucosa as well as low concentration of zinc in plasma such as in infants or children who are experiencing diarrhea. This paper aims to determine the effects of zinc supplementation on pro-inflammatory cytokines (TNF-α, IL-1 and IL-6) in mice with E. coli-LPS-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Innate immune cells usually use pattern recognition receptors (PRRs) to recognize pathogen-associated molecular patterns (PAMP) ( Almeida et al, 2020 ). After the virus enters the infected cells through interaction with the receptor, it can further promote the innate immune cells to secrete cytokines and chemokines, such as IL-1β, IL-6, TNF-α, and IFN-β, which lead to the activation of inflammasomes ( Yusuf et al, 2019 ). The phagocytes can phagocytize and degrade the viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune cells usually use pattern recognition receptors (PRRs) to recognize pathogen-associated molecular patterns (PAMP) ( Almeida et al, 2020 ). After the virus enters the infected cells through interaction with the receptor, it can further promote the innate immune cells to secrete cytokines and chemokines, such as IL-1β, IL-6, TNF-α, and IFN-β, which lead to the activation of inflammasomes ( Yusuf et al, 2019 ). The phagocytes can phagocytize and degrade the viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from in vitro studies sμggests that SARS-CoV-2 replication can be inhibited by increase in zinc concentration [ 81 ]. Zinc supplementation studies have shown decreased oxidative stress due to its participation in free radical scavenging and pro-inflammatory markers levels such as IL-1, IL-6 and TNFα, even during infection [ 82 , 83 ]. Zinc may therefore reduce the inflammation in the gut caused by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effective action of Zn along with Pc lowered the amount of the cytokine like TNF-α as reported earlier. 57 In the case of histopathological images, the administration of ZnPcN and formulation of ZnPcPNs might ameliorate damaged hepatic lobules with recovered cytoplasm and reduced residual inflammation considering the central vein and moderately dilated sinusoids. The administration of ZnPcN and formulation of ZnPcPNs reduced the ROS damage and oxidative stress that prevented further histological and renal damage.…”
Section: Semmentioning
confidence: 99%